2020
DOI: 10.2174/2210315510666191227150222
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Medicinal Plants Containing Phenolic Compounds

Abstract: Background: Medicinal plants have been used to treat diseases for centuries. They are important sources in terms of their pharmacological effects and also have many microbial agents. Recently, the development of drug resistance has begun to spread in human pathogens against used antibiotic and this situation has led to the increasingly necessitating the new researches for novel antimicrobial substances from natural products containing plants. Objective: The purpose of this review is to determine the antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…These compounds are characterized by the presence of one or more hydroxyl (-OH) groups attached to a sixcarbon aromatic ring (Dikpınar & Süzgeç-Selçuk, 2020;Gulcin, 2020). Phenolic compounds are present either as unconjugated glycosides or bound to sugars, such as glucose, galactose, rhamnose, xylose, or arabinose in glycosidic forms (González-Sarrías et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are characterized by the presence of one or more hydroxyl (-OH) groups attached to a sixcarbon aromatic ring (Dikpınar & Süzgeç-Selçuk, 2020;Gulcin, 2020). Phenolic compounds are present either as unconjugated glycosides or bound to sugars, such as glucose, galactose, rhamnose, xylose, or arabinose in glycosidic forms (González-Sarrías et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds were initially investigated for their involvement in browning reactions and in providing a color and bitter taste; however, it was later shown that phenolic compounds protect plants against environmental factors such as low temperatures and free oxygen radicals [ 6 ]. More than 8000 different compounds are collectively referred to as phenolic compounds, making them the most significant class of phytochemicals [ 7 , 8 ], and the most prevalent in the plant kingdom [ 9 ]. Shahidi and Zhong [ 10 ] reported that phenolic compounds are ideal dietary antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Among these substances, phenolic compounds, considered the largest group of plant secondary metabolites, are presented as some of the most interesting bioactive compounds. These molecules have been studied for their extensive bioactive properties, such as antioxidant [5,6], antimicrobial [7,8], anti-inflammatory [9][10][11], and antihypertensive [12,13] effects, among others, which have a great potential for the pharmaceutical, cosmetic, and food industries.…”
Section: Introductionmentioning
confidence: 99%